2019
DOI: 10.3390/w11081642
|View full text |Cite
|
Sign up to set email alerts
|

Use of Visible Light Modulation Techniques in Urea Photocatalytic Degradation

Abstract: The aim of this work was to analyze the effect of visible LED dimming duty-cycle modulation techniques in a photocatalytic system for urea degradation using a visible light photocatalyst immobilized on macroscopic supports. For this reason, the effect of different LED dimming techniques was investigated and compared in terms of urea degradation together with ammonia and nitrate production during the irradiation time. The experimental results evidenced that using a visible LED dimming modulation with variable-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The methods for fixing N-doped TiO 2 particles on the chosen polymeric substrate can be developed starting from those studied for the immobilization of undoped TiO 2 . They may vary from simple, such as the solvent-casting method [46][47][48][49][50] or sol-gel techniques [58], to more complex, specialized and expensive methods, such as magnetron sputtering [59] and gelation of a catalyst in a polymeric substrate and subsequent extraction with supercritical CO 2 [55,56,60]. It is worth noting that the method for immobilizing N-doped TiO 2 on a polymeric support influences the photocatalytic activity, which also depends on the type of substrate and pollutant to be degraded.…”
Section: General Overview On Methods For the Immobilization Of N-doped Tio 2 On Polymeric Supportsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methods for fixing N-doped TiO 2 particles on the chosen polymeric substrate can be developed starting from those studied for the immobilization of undoped TiO 2 . They may vary from simple, such as the solvent-casting method [46][47][48][49][50] or sol-gel techniques [58], to more complex, specialized and expensive methods, such as magnetron sputtering [59] and gelation of a catalyst in a polymeric substrate and subsequent extraction with supercritical CO 2 [55,56,60]. It is worth noting that the method for immobilizing N-doped TiO 2 on a polymeric support influences the photocatalytic activity, which also depends on the type of substrate and pollutant to be degraded.…”
Section: General Overview On Methods For the Immobilization Of N-doped Tio 2 On Polymeric Supportsmentioning
confidence: 99%
“…Chemical-physical characterization results and visible-light-driven methylene blue degradation tests evidenced that the best performances are achieved when an optimal N-doped TiO 2 amount is dispersed in acetone to obtain a suspension that is dropped on the PS surface [46]. Starting from these preliminary results, N-doped TiO 2 was also immobilized on the surface of PS spheres and PS pellets in cylindrical shape by using the same preparation method [48][49][50]. The photocatalytic activity under visible light of such systems was evaluated in the methylene blue and urea degradation as well as in the inactivation of E. coli in real municipal wastewater, evidencing the stability of the obtained systems after several reuse cycles [48][49][50].…”
Section: N-doped Tio 2 /Ps (Polystyrene)mentioning
confidence: 96%
See 2 more Smart Citations
“…The accumulation of urea from urinary excretions becomes a problem in cities with a high population rate, where biodegradation is not sufficient to mitigate the associated ecological risks. In fact, numerous investigations in recent years have focused on the development of heterogeneous photocatalysts powered by sunlight for effective environmental purification of wastewater. In this sense, some efforts have been directed to the development of nanostructures based on Bi 2 WO 6 , which have revealed that they could function as excellent photocatalytic materials exhibiting enhanced activities for advanced oxidation of many contaminants. However, despite the absorption of solar energy by these materials, an electron is promoted from the valence band to the conduction band (e CB – ), leaving an electronic deficiency in the valence band called a hole (h VB + ) (eq ). The recombination of the latter charge carriers can greatly decrease the overall efficiency of the solar to chemical energy conversion .…”
Section: Introductionmentioning
confidence: 99%